MOA-2011-BLG-322Lb: a 'second generation survey' microlensing planet. Issue 1 (30th January 2014) - Shvartzvald, Y.; Maoz, D.; Kaspi, S.; Sumi, T.; Udalski, A.; Gould, A.; Bennett, D. P.; Han, C.; Abe, F.; Bond, I. A.; Botzler, C. S.; Freeman, M.; et al.
Abstract: Global 'second-generation' microlensing surveys aim to discover and characterize extrasolar planets and their frequency, by means of round-the-clock high-cadence monitoring of a large area of the Galactic bulge, in a controlled experiment. We report the discovery of a giant planet in microlensing event MOA-2011-BLG-322. This moderate-magnification event, which displays a clear anomaly induced by a second lensing mass, was inside the footprint of our second-generation microlensing survey, involving MOA, OGLE and the Wise Observatory. The event was observed by the survey groups, without prompting alerts that could have led to dedicated follow-up observations. Fitting a microlensing model to the data, we find that the time-scale of the event was t E  = 23.2 ± 0.8 d, and the mass ratio between the lens star and its companion is q  = 0.028 ± 0.001. Finite-source effects are marginally detected, and upper limits on them help break some of the degeneracy in the system parameters. Using a Bayesian analysis that incorporates a Galactic structure model, we estimate the mass of the lens at $0.39^{+0.45}_{-0.19}\, {\rm M}_{\odot }$, at a distance of 7.56 ± 0.91 kpc. Thus, the companion is likely a planet of mass $11.6^{+13.4}_{-5.6}\, M_{\rm J}$, at a projected separation of $4.3^{+1.5}_{-1.2}$ au, rather far beyond the snow line. This is the first pure-survey planet reported from a second-generation microlensing survey, and shows that survey data alone can be sufficient to characterize a planetary model. With the detection of additional survey-only planets, we will be able to constrain the frequency of extrasolar planets near their systems' snow lines.